Extrinsic ion migration in perovskite solar cells. Issue 5 (20th April 2017) - Li, Zhen; Xiao, Chuanxiao; Yang, Ye; Harvey, Steven P.; Kim, Dong Hoe; Christians, Jeffrey A.; Yang, Mengjin; Schulz, Philip; Nanayakkara, Sanjini U.; Jiang, Chun-Sheng; Luther, Joseph M.; Berry, Joseph J.; et al.
Abstract : Extrinsic ions ( e.g., Li + ) migrate across perovskite solar cells and modify the TiO2 layer, affecting device performance and hysteresis. Abstract : The migration of intrinsic ions ( e.g., MA +, Pb 2+, I − ) in organic–inorganic hybrid perovskites has received significant attention with respect to the critical roles of these ions in the hysteresis and degradation in perovskite solar cells (PSCs). Here, we demonstrate that extrinsic ions ( e.g., Li +, H +, Na + ), when used in the contact layers in PSCs, can migrate across the perovskite layer and strongly impact PSC operation. In a TiO2 /perovskite/spiro-OMeTAD-based PSC, Li + -ion migration from spiro-OMeTAD to the perovskite and TiO2 layer is illustrated by time-of-flight secondary-ion mass spectrometry. The movement of Li + ions in PSCs plays an important role in modulating the solar cell performance, tuning TiO2 carrier-extraction properties, and affecting hysteresis in PSCs. The influence of Li + -ion migration was investigated using time-resolved photoluminescence, Kelvin probe force microscopy, and external quantum efficiency spectra. Other extrinsic ions such as H + and Na + also show a clear impact on the performance and hysteresis in PSCs. Understanding the impacts of extrinsic ions in perovskite-based devices could lead to new material and device designs to further advance perovskite technology for various applications.